Differentiating instruction - Frost, Frank; Kiernan, Leslie J. (Virginia : Association for Supervision and Curriculum Development, 1997)
The videotapes take viewers into eight classrooms to explore the concepts of differentiated instruction and to see instructional and management techniques that teaches use in creating differentiated classrooms
vol. 1. Creating multiple paths for learning - vol. 2. Instructional and management strategies
Accompanied by 1 facilitators guide and 1 book. Title : How to differentiate instruction in mixed-ability classrooms by Carol Ann Tomlinson
Editor, Skip Heerman ; writer, Frank Frost, Leslie J. Kiernan
Keywords: Mixed ability grouping in education -- United States; Learning ability -- United States; Classroom management -- United States